A neoteric multidrug combination: novel approach to limited cutaneous systemic scleroderma involving the face. (31st March 2016) - Kumar, M Hari; Kumar, M Siva; Kumar, Sabitha Hari; Kumar, Kingsly Selva
Abstract : Limited cutaneous scleroderma is a subtype of scleroderma limited to the skin of the face, hands, feet and forearms. We present a case of a 45-year-old woman affected by limited cutaneous systemic scleroderma involving the orofacial region and causing restricted mouth opening. The patient showed noteworthy improvement of the skin lesion by use of a combination of intralesional corticosteroid with hyaluronidase and various multiantioxidants, resulting in amelioration of her mouth opening problem. The patient gave her full informed written consent to this report being published.